First record of Serratospiculum tendo (Nematoda: Diplotriaenidae) in Peru - Gomez-Puerta, Luis A. (2014)
We report for first time the presence of nematode, Serratospiculum tendo Nitzsch, 1819, parasitizing air sacs of a Peregrine Falcon (Falco peregrinus Tunstall, 1771). Six nematodes (2 males and 4 females) were collected and identified as S. tendo. The discovery of this nematode is the first record in Peru.